Influence of swimming speed on the affected- and unaffected-arm stroke phases of competitive unilateral arm amputee front crawl swimmers - Osborough, C. D.; Payton, C. J.; Daly, D. J. (Biomechanics and Medicine in Swimming XI, 2010)
The purpose of this study was to determine whether the arm stroke phases used by competitive unilateral arm amputee crawl swimmers differed between their affected and unaffected sides and whether these phases changed with an increase in speed. Thirteen highly-trained swimmers were video-taped underwater from two side-views during five increasingly faster 25 m front crawl trials. At all swimming speeds, the stroke phases of the affected and unaffected arms differed significantly. As speed increased, the duration of the affected-arm`s Entry and Glide phase and the unaffected-arm`s Pull phase decreased significantly; the duration of both arms` Push phase increased significantly. The amputees used a coordination strategy that asymmetrically adjusted their arm movements to maintain the stable repetition of their overall stroke cycle at different speeds.